2006
DOI: 10.1177/107110070602700406
|View full text |Cite
|
Sign up to set email alerts
|

Results and Outcomes After Operative Treatment of High-Energy Tibial Plafond Fractures

Abstract: Tibial plafond fractures are difficult to manage and may have serious complications. We identified more complications, more secondary procedures, and worse outcomes in patients with articular and metaphyseal comminution (type C3). ORIF was associated with fewer complications and less post-traumatic arthritis when compared to EF, possibly reflecting a selection bias for open injuries and more severely comminuted fractures to be managed with EF. ORIF with appropriate soft tissue handling resulted in acceptable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 59 publications
0
83
0
2
Order By: Relevance
“…Other series utilizing a staged protocol have demonstrated a 26% rate of complications in C3 distal tibia fractures and open fractures have demonstrated a 10.5% infection rate. 9, 25 Patterson reported good results on a series of 22 C3 pilon fractures, 6 of which were open, and had 0 soft tissue complications. 24 More recently, Gardner et al 26 reported on their series of patients with open AO type C3 fractures.…”
Section: Discussion and Historical Comparisonmentioning
confidence: 97%
See 2 more Smart Citations
“…Other series utilizing a staged protocol have demonstrated a 26% rate of complications in C3 distal tibia fractures and open fractures have demonstrated a 10.5% infection rate. 9, 25 Patterson reported good results on a series of 22 C3 pilon fractures, 6 of which were open, and had 0 soft tissue complications. 24 More recently, Gardner et al 26 reported on their series of patients with open AO type C3 fractures.…”
Section: Discussion and Historical Comparisonmentioning
confidence: 97%
“…Isolation of open pilon fractures placed their quality of life just better than a nursing home patient and worse than someone with congestive heart failure. Harris et al 25 reported functional outcomes after high-energy pilon fractures. They treated 88% of type C3 fractures with external fixation and noted greatest functional impairment in type C3 regardless of fixation method.…”
Section: Discussion and Historical Comparisonmentioning
confidence: 98%
See 1 more Smart Citation
“…[34] These results were evident in any form of external fixation technique used and whether uniplanar, circular (hybrid/ Illizarov), or LIFEF frames were utilized. Guo et al [29] Harris et al [23] Koulouvaris et al [24] Richards et al There have been important advances in the surgical management and strategies of pilon fractures including hybrid external fixators, minimally invasive and limited internal fixations, staged ORIF, and arthroscopy-assisted procedures, all of which have attempted to improve the early and late outcomes of surgical treatment of such fractures. As the surgical methods continue to evolve and outcomes improve, it remains increasingly difficult to answer the ultimate question "what is the best surgical procedure to manage pilon fractures?…”
Section: Discussionmentioning
confidence: 99%
“…Looking specifically at some of the high-energy injuries reported in the foot and ankle literature and trying to extrapolate the data are difficult because the authors often fail to segregate the results of their elderly patients. 42,43 Second, there is no consensus regarding the specific age that qualifies when a patient is to be considered ''geriatric.'' Although some patients attaining the age of 62 years may be eligible for Medicare claims and could be considered elderly individuals, there is no real agreement as to the age that is necessary for someone to reach and crossover from middle age to elderly individuals.…”
mentioning
confidence: 99%